2014
DOI: 10.2147/ceg.s41780
|View full text |Cite
|
Sign up to set email alerts
|

The role of everolimus in liver transplantation

Abstract: During the last 5 decades, liver transplantation has witnessed rapid development in terms of both technical and pharmacologic advances. Since their discovery, calcineurin inhibitors (CNIs) have remained the standard of care for immunosuppression therapy in liver transplantation, improving both patient and graft survival. However, adverse events, particularly posttransplant nephrotoxicity, associated with long-term CNI use have necessitated the development of alternate treatment approaches. These include combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 102 publications
2
21
0
2
Order By: Relevance
“…in the treatment of some human neoplasms in selected cases (early stage NSCLC [16], advanced renal cell carcinoma [17], hormone receptor-positive and human epidermal growth factor receptor 2-negative advanced breast cancer [18], Kaposi's sarcoma in renal-transplant recipients [19]) and in the prevention of transplant rejection [20,21]. mTOR exists as a part of two distinct protein complexes, named mTOR complex 1 (mTORC1) and mTOR complex 2.…”
Section: Methods and Analysismentioning
confidence: 99%
“…in the treatment of some human neoplasms in selected cases (early stage NSCLC [16], advanced renal cell carcinoma [17], hormone receptor-positive and human epidermal growth factor receptor 2-negative advanced breast cancer [18], Kaposi's sarcoma in renal-transplant recipients [19]) and in the prevention of transplant rejection [20,21]. mTOR exists as a part of two distinct protein complexes, named mTOR complex 1 (mTORC1) and mTOR complex 2.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Thus, sirolimus was not approved in liver transplantation, although recent studies using lower doses showed an improved safety profile[66,67]. Viceversa, everolimus provides a new therapeutic option for liver transplant recipients, when introduced early after liver transplantation[68] particularly with respect to posttransplant nephrotoxicity and other adverse events associated with long- term administration of CNIs.…”
Section: Immunosuppressive Therapy and Metabolic Alterationsmentioning
confidence: 99%
“…4,5, 6 The comparators for such evaluations are the mammalian target of Rapamycin (mTOR) inhibitors; sirolimus and everolimus (EVR).Everolimus gained approval for use in liver transplant patients following its introduction as an immunosuppressant in renal transplantation. 7 Use of EVR is approved in combination with reduced dose tacrolimus (RTAC) after 30 days of liver transplant. 7 Several studies have looked at the efficacy and safety of either EVR monotherapy or reduced CnI dose combination therapy (EVR+RTAC) compared to the standard CnI therapy post-liver transplantation.…”
Section: Introductionmentioning
confidence: 99%